Signs of the times : words taught by the spirit - Villagracia, Apolonio; Abangley, Rudy G.; Diaz, Jade M.; Flores, Delia Paz A.; Carpizo, Danilo O. (Sampaloc, Manila : Rex Book Store, Inc., 2016)
"Signs of the Times, a religious education series from Kinder to Grade 12, is a product of humble desire to educate every person of his/her dignity and mission as a son/daughter of God (2 Corinthians 6:18).
Includes bibliographical references.
English text.
Keywords: Christian education; Religious education